Effect of Intermittent Hypobaric Hypoxia Exposure on HIF-1α, VEGF, and Angiogenesis in the Healing Process of Post-Tooth Extraction Sockets in Rats - Linawati, Linawati; Sitam, Suhardjo; Mulyawan, Wawan; Purba, Ambrosius; Syawqie, Achmad; Handharyani, Ekowati; Subiakto, Yuli; Amaliya, Amaliya (European Journal of Dentistry, 2023)
Objective The aim of this study was to investigate the effect of intermittent hypobaric hypoxia (IHH) exposure on the expression of hypoxia-induced factor-1α (HIF-1α) messenger RNA (mRNA), vascular endothelial growth factor-a (VEGF-a) mRNA, and angiogenesis after tooth extraction in rats.Materials and Methods On 45 male Sprague-Dawley rats were performed the removal of the maxillary left first molar, and then they were randomly divided into 9 groups, namely: 4 groups that were exposed to IHH for 30 minutes every day in the Hypobaric Chamber at an altitude of 18,000 feet, with 1 time hypobaric hypoxia (HH), 3 times HH, 5 times HH, and 7 times HH; 4 normoxia groups that were terminated on days 1, 3, 5, and 7 after tooth extraction; and the 1 control group. Real-time polymerase chain reaction measured the molecular changes in the socket tissue after tooth extraction in rats to evaluate the expression of HIF-1α mRNA and VEGF mRNA. Histological changes with hematoxylin and eosin staining were noted to evaluate the amount of angiogenesis in the socket after tooth extraction. Molecular and histological parameters were calculated at the end of each experiment on days 0, 1, 3, 5, and 7 after tooth extraction, which exhibited the improvement phase of the wound-healing process.Results Increases in the expression of HIF-1α mRNA, VEGF mRNA, and angiogenesis were found in the IHH group compared with the normoxia group and the control group. The expression of HIF-1α mRNA increased significantly (p < 0.05) in the group after one time HH exposure on day 1, then decreased in the IHH group (three times HH exposure, five times HH exposure, and seven times HH exposure) approaching the control group. The expression of VEGF mRNA and angiogenesis began to increase after one time HH exposure on day 1, and increased again after three times HH exposure on day 3, then increased even more after five times HH exposure on day 5, and increased very significantly (**p < 0.05) after seven times HH exposure on day 7. It showed that repeated or intermittent exposure to HH conditions induced a protective response that made cells adapt under hypoxia conditions.Conclusion IHH exposure accelerates the socket healing of post-tooth extraction, which is proven by changes in HIF-1α mRNA expression and increase in VEGF mRNA expression as stimuli for angiogenesis in post-tooth extraction sockets under hypobaric hypoxic condition, which also stimulates the formation of new blood vessels, thereby increasing blood supply and accelerating wound healing.
Keywords: hypoxia; HIF-1α; VEGF-a; tooth extraction; wound healing